Pertinences et apories d’une lecture féministe de La Princesse de Clèves au regard de la théorie queer - Dubois, François-Ronan (Romanica Silesiana)
Insights and Limitations of a Feminist Reading of La Princesse de Clèves According to Queer Theory Often interpreted from the feminist perspective, La Princesse de Clèves has come to represent a tale of feminine oppression and feminine heroism. As enlightening as such a reading may be, this paper seeks to further explore the gendered identities at stake in the novel, with the help of a Nietzschean queer theory. Underlining the role of Madame de Clèves in the economy of desire that constructs space and power in the world of the text is an important step toward a more subtle understanding of the narrative. Key words: Clèves, Lafayette, queer, feminism, 17th century.